X-Parameter Measurement of Pulse-Compression Nonlinear Transmission Lines - Ming Li; Rony E. Amaya; Robert G. Harrison; N. Garry Tarr (Journal of Electrical and Computer Engineering)
X-parameters provide a powerful and eminently practical solution for interoperable measurement, modeling, and simulation of nonlinear microwave and RF components. Using X-parameters to do large-signal measurements has been brought into the spotlight. This paper introduces a new X-parameter application: measuring large-signal behaviour of pulse-compression nonlinear transmission lines (NLTLs). A specially configured Nonlinear Vector Network Analyzer (NVNA) was used to measure the X-parameters in the frequency-domain, and then the measured data was transformed into a nonlinear time-domain waveform. The results show both rise-time and fall-time reduction (double-edge compression) as expected and indicate that this newly developed X-parameter method implemented with an NVNA could correctly predict NLTLs' pulse-compression performance.